Корректировочный курс грамматики в системе обучения иностранных студентов первого курса - Петрушова, О.В.; Черненко, И.И.; Хуммедова, Я.; Петрушова, О.В.; Черненко, I.I.; Хуммедова, Я.; Petrushova, O.V.; Chernenko, I.I.; Hummedova, Y. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2012)
В статье рассматривается проблема обучения иностранных студентов (в частности, студентов из Туркменистана) первого курса вузов, не обучавшихся на подготовительных факультетах, имеющих разный уровень подготовки по русскому языку, и обеспечения их методическими матеріалами “Корректировочный курс грамматики”.
Коректувальний курс гра- матики в системі навчання іноземних студентів першого курсу.
The Corrective Grammar Course in the System of Teaching the First-year Foreign Students.
The problem of teaching the first-year foreign students (students from Turkmenistan in particular) has been examined in the article. These students have not had the preliminary courses; they have a different level of Russian language background. Providing the students with the methodological materials on the subject “Corrective grammar course” has also been considered in the article.
Keywords: уровень подготовки; русский язык; методические материалы; корректировочный курс; рівень підготовки; російська мова; методичні матеріали; коректувальний курс; level of background; Russian language; methodological materials; corrective course